THE ANALYSIS OF LEARNING AND BEHAVIOR: SKINNER’S LAW OF POSITIVE REINFORCEMENT - Turdiyeva Zahro Mirsoliyevna (TADQIQOTLAR, 2025)
This article explores the theories of Burrhus Frederic Skinner, particularly his work on operant conditioning and its application in educational settings. Skinner’s emphasis on positive reinforcement and structured, error-free learning materials has significantly influenced classroom management and teaching practices, especially for students with learning difficulties. The article also highlights objections to Skinner’s theory, such as the undervaluation of risk-taking and failure as essential components of learning, the reduction of learning processes to conditioning, and concerns about over-reliance on external rewards. The discussion further contrasts Skinner’s behaviorist approach with contemporary educational philosophies emphasizing intrinsic motivation, concept development, and the invisible aspects of learning.